“The broken schippus he ther fonde”: Shipwrecks and the Human Costs of Investment Capital in Middle English Romance - Richmond, Andrew M. (Neophilologus, 2015)
Featuring prominently in the romance imagination as terrifying obstacles in the hero’s path, shipwrecks are nevertheless often presented from the salvager’s perspective. Romances abound with knights, clerks, and merchants who obsessively observe nearby beaches and cautiously (yet excitedly) examine the contents of wrecked vessels. Washed ashore, such fruits of maritime disaster delineate medieval English conceptions of seashores as dangerous yet profitable spaces, wherein seaside harvests of (un)natural resources help to stimulate local economic networks. Designations of these shipwrecks as “magical” or “fortuitous” cannot, however, completely elide the source of such wealth in others’ suffering—an unavoidable implication that interrogates contemporary means of attaining investment capital. As such, this paper examines how the littoral space of the seashore is cast as a source of perilous and problematic material bounty in many Middle English romances.
Keywords: Emaré; Geoffrey Chaucer; John Gower; Middle English romance; Shipwrecks; Sir Amadace; dept.eng

Dead Narratives: Defining Humanity through Stories - Ellis, Scott (The Apocalypse in Film: Dystopias, Disasters, and Other Visions about the End of the World, 2015)
We live in a world at risk. Dire predictions about our future or the demise of planet earth persist. Even fictional representations depict narratives of decay and the end of a commonly shared social reality. Along with recurring Hollywood blockbusters that imagine the end of the world, there has been a new wave of zombie features as well as independent films that offer various visions of the future. The Apocalypse in Film: Dystopias, Disasters, and Other Visions about the End of the World offers an overview of Armageddon in film from the silent era to the present. This collection of essays discusses how such films reflect social anxieties—ones that are linked to economic, ecological, and cultural factors. Featuring a broad spectrum of international scholars specializing in different historical genres and methodologies, these essays look at a number of films, including the silent classic The Four Horsemen of the Apocalypse, the black comedy Dr. Strangelove or: How I Learned to Stop Worrying and Love the Bomb, the Mayan calendar disaster epic, 2012, and in particular, Lars Von Trier’s Melancholia, the focus of several essays.As some filmmakers translate the anxiety about a changing global climate and geo-political relations into visions of the apocalypse, others articulate worries about the planet’s future by depicting chemical warfare, environmental disasters, or human made destruction. This book analyzes the emergence of apocalyptic and dystopic narratives and explores the political and social situations on which these films are based. Contributing to the dialogue on dystopic culture in war and peace, The Apocalypse in Film will be of interest to scholars in film and media studies, border studies, gender studies, sociology, and political science.

Sabbatical Leave Report - Hochman, Will (Distribution: fall-spring-15 ; English., 2015)
From the report: "My goal was to develop, reserach and write my next study on J.D. Salinger. With the aid of research and [sic] on Salinger's letters at the Morgan Library and The Firestone Library (Princeton), and several visits to his Cornish home, I was able to finish one manuscript, begin another, and start a Salinger essay designed to attract interest in my manuscript. I am happy to report that I completed my next manuscript, Harvesting Salinger's Rye, because I earned the tremendous good fortune to recieve support from SCSU."
Keywords: dept.eng; faculty_collection; sabbatical_report

American Woman Suffrage Postcards: A Study and Catalog - Florey, Kenneth (McFarland & Company, Inc., Publishers, 2015)
"American women's suffrage activists were fascinated with suffrage themed postcards. They collected them, exchanged them, wrote about them, used them as fundraisers and organized 'postcard day' campaigns. The cards they produced were imaginative and ideological, advancing arguments for the enfranchisement of women and responding to antisuffrage broadsides. Publishers were also interested in suffrage cards, recognizing their profit potential"--
Keywords: Catalogs; Catalogs; Postcards; History; History; Postcards; Pictorial works; Pictorial works; Women; Political aspects; Suffrage; United States; Women; dept.eng; faculty_collection

Perennial - Shipley, Vivian (Negative Capability Press, 2015)
Keywords: dept.eng; faculty_collection

The Poet - Shipley, Vivian (Louisiana Literature Pres, 2015)
Keywords: dept.eng; faculty_collection

Invisible debility: attitudes toward the underrepresented in library workplaces - Brown, Mary E (Public Library Quarterly, 2015)
The American Library Association is committed to recruiting persons of color and those with disabilities to the profession, yet these groups are underrepresented among librarians. While intentional discrimination was the impetus for the Civil Rights Act of 1964, empirical studies in the workplace have exposed continued discrimination through unconscious bias. Extending such research to the library profession raises the question: How do librarians perceive the underrepresented as potential fellow library staff? In my recently conducted study of public library staff and future librarians, participants agreed that library staff should represent the diversity of the communities served; there was little support, however, for actively attempting to advance proportional representation through education or hiring. © , Published with license by Taylor & Francis.
Keywords: dept.eng; employment discrimination; hiring bias; peer-reviewed; underrepresentation of minorities in library employment

Is Personality a System? Stability, Process and Plasticity. - Larocco, Steven (Integrative psychological & behavioral science, 2015)
The nomothetic thrust of personality research has been the subject of some significant recent criticism. One major problem is the failure in much personality research to sufficiently scrutinize its methods and its background beliefs. This produces conceptual schematizations of personality that do not sufficiently take into account the disunity and plasticity that affects what is construed as personality; it also underplays the necessity of more fully theorizing the network of infrapsychic and transpersonal systems, processes, structures, templates, interfaces, flows of stimuli, qualities of embodiment and contingencies that dynamically manifest as personality. It is through unfolding the complexity inherent in this network that personality theorization can move forward in new ways. This paper provides a provisional, beginning taxonomy of this network in order to start a research dialogue about personality that doesn't begin with the operative background beliefs of nomothetic methodology, that doesn't tacitly or overtly construe the individual to be a self-regulating, homeostatic system, and that resists presupposing personality as a cohesive, stable quality of personhood.
Keywords: *Personality; *Psychological Theory; Contingency; Embodiment; Five-factor model; Humans; Personality; Personality/cl [Classification]; Plasticity; Plasticizer; Psychological Theory; Stabilizer; classification; dept.eng; human; personality; psychological theory